Harnessing wine yeasts: Unveiling their potential as lipid supplements - Julian J. Pietersen; Stéphanie Rollero; Benoit Divol (International Journal of Food Microbiology, 2026)

Uncovering genetic and phenotypic diversity connections in Lachancea thermotolerans: impact on wine aromatics - Theo R. Jacobs; Stéphanie Rollero; Arnaud Delaherche; Mathabatha E. Setati; Benoit Divol (Food Microbiology, 2026)

The cellular symphony of redox cofactor management by yeasts in wine fermentation - James D. Duncan; Mathabatha E. Setati; Benoit Divol (International Journal of Food Microbiology, 2025)

Oxygen alters redox cofactor dynamics and induces metabolic shifts in Saccharomyces cerevisiae during alcoholic fermentation - James D. Duncan; Hugo Devillers; Carole Camarasa; Mathabatha E. Setati; Benoit Divol (Food Microbiology, 2024)

Differences in the management of intracellular redox state between wine yeast species dictate their fermentation performances and metabolite production - Viwe Tyibilika; Mathabatha E. Setati; Audrey Bloem; Benoit Divol; Carole Camarasa (International Journal of Food Microbiology, 2024)

Corrigendum to “Redox cofactor metabolism in Saccharomyces cerevisiae and its impact on the production of alcoholic fermentation end-products” [Food Res. Int. 163 (2023) 112276] - James D. Duncan; Mathabatha E. Setati; Benoit Divol (Food Research International, 2023)

Redox cofactor metabolism in Saccharomyces cerevisiae and its impact on the production of alcoholic fermentation end-products - James D. Duncan; Mathabatha E. Setati; Benoit Divol (Food Research International, 2023)

Phenotypic characterization of cell-to-cell interactions between two yeast species during alcoholic fermentation - Natasha Alethea Luyt; Sandra Beaufort; Benoit Divol; Mathabatha Evodia Setati; Patricia Taillandier; Florian Franz Bauer (World Journal of Microbiology and Biotechnology, 2021)

A comparison of the nitrogen metabolic networks of Kluyveromyces marxianus and Saccharomyces cerevisiae - Stéphanie Rollero; Audrey Bloem; Anne Ortiz‐Julien; Florian F. Bauer; Carole Camarasa; Benoit Divol (Environmental Microbiology, 2019)
Summary In grape must, nitrogen is available as a complex mixture of various compounds (ammonium and amino acids). Wine yeasts assimilate these multiple sources in order to suitably fulfil their anabolic requirements during alcoholic fermentation. Nevertheless, the order of uptake and the intracellular fate of these sources are likely to differ between strains and species. Using a two‐pronged strategy of isotopic filiation and RNA sequencing, the metabolic network of nitrogen utilization and its regulation in Kluyveromyces marxianus were described, in comparison with those of Saccharomyces cerevisiae . The data highlighted differences in the assimilation of ammonium and arginine between the two species. The data also revealed that the metabolic fate of certain nitrogen sources differed, thereby resulting in the production of various amounts of key wine aroma compounds. These observations were corroborated by the gene expression analysis.

PCR detection of enzyme-encoding genes in Leuconostoc mesenteroides strains of wine origin - Phillip Senzo Mtshali; Benoit Divol; Maret du Toit (World Journal of Microbiology and Biotechnology, 2012)